Luxmeter Design with Proximity Sensor to Efficiently Test Light Intensity and Distance on Lamp Operation in Hospitals - Dika Surya Rizky Rahayu; M. Ridha Mak'ruf; Syaifudin Syaifudin (International Journal of Advanced Health Science and Technology, 2021)
The lighting of the operating/surgical site depends on the quality of the lighting from the overhead light source and the reflection from the curtain. Light measurement on the operating table is very necessary because it generates light that is irradiated into the cutting wound without dazzling the cutting surface so that pathological conditions can be recognized and must provide depth contrast and anatomical relationships, to ensure this proper calibration method is needed. Long-term use of medical devices can cause changes in accuracy. Therefore, the author makes a tool to measure the intensity of light which is equipped with a distance meter. The purpose of this study was to develop a measuring instrument for measuring the intensity of light in operating lamps, namely a luxmeter by making Luxmeter equipped with a TFT Display Distance Sensor. This tool uses an ultrasonic sensor HC-SR04 to measure the distance between the light source and the sensor module and the MAX44009 sensor to measure the light intensity of the operating lamp displayed on the TFT screen. Based on the module distance setting to the roll meter, the distance error value for the measurement of the Surabaya electromedical engineering workshop lamp at the 75 cm roll meter distance setting is 0.0127% for the 100 cm roll meter distance setting is 0.0045%. The error rate of the light intensity module on the results of the measurement of light intensity on the luxmeter by setting the roll meter distance of 75 cm between the tool and the lamp of the electromedical engineering workshop is getting an error value of 0.082% lux and for the light intensity on the results of the measurement of light intensity on the luxmeter with a roll meter distance setting of 100 cm between the tool and the lamp in the electromedical engineering workshop, that is, the error value of lux is 0.055%. The design of a luxmeter equipped with a proximity sensor can measure the intensity of light and the distance between the tool and the light source and can assist in the learning process with a more effective Luxmeter design that will assist electromedics in testing operating lamps in hospitals to be more efficient.